(untitled) (Research, Society and Development, 2020)
The sensory characterization of a product serves as a tool to improve its quality and observe the effects of its processing on the attributes of taste, aroma, texture and appearance. This work was intended to use the Quantitative Descriptive Analysis (QDA) to trace the sensory profile of jambolan jams. For the optimization of jams, the response surface methodology was used with complete factorial planning 23. Regarding the characteristics of the jellies, twelve descriptors were obtained, which showed the similarities and differences between the jams. Nine evaluators were selected based on the ability to discriminate and reproduce the assessment. The data were analyzed by ANAVA and Tukey’s 5% significance test. From the results obtained by the sensory profile and affective test, significant differences were observed between the proposed formulations, with the F2 formulation (with a pulp/sugar ratio of 40/60, without addition of citric acid and with 3% of passion fruit albedo) presenting the best averages in sensory attributes, with higher levels of brightness, aroma, sweet taste, color and viscosity.